Adaptation and validity of the Trait Meta-Mood scale for Brazilian adolescents - Câmara, Sheila Gonçalves; Carlotto, Mary Sandra; Cabello, Rosario; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2023)
The current study aimed to present the process of adaption and validity evidence of the Trait Meta-Mood Scale (TMMS-24) for the population of Brazilian school adolescents. The study included 4681 students aged 10 to 19 years old, attending public schools in 12 cities in the state of Rio Grande do Sul, Brazil. According to the original scale, the exploratory and confirmatory factorial analyses indicated adequate fit indexes and satisfactory reliability for the model composed of 24 items and three factors (attention, clarity, and repair). The scale showed a significant positive correlation with life satisfaction and psychological well-being. The results reveal that the TMMS-24 is adequate for the assessment of emotional intelligence among Brazilian adolescents and may contribute to research and interventions regarding emotional competencies among this population.